Application of six sigma model in production and quality of the stabiliser - Muhammad Firdaus, Azmi (2015)
Six Sigma applications is a one of the effective Total Quality Management tools in order to improve quality of the product and productivity in industry. However, while many benefits of Six Sigma are increasingly reported in other country, it is not very common among local company because lack of exposure and many companies in Malaysia afraid to take a high risk. Furthermore, although there have been numerous case studies, comprehensive discussions, books and websites addressing Six Sigma, a very little academic research has been done to examine the impact of the Six Sigma application in local industry. This project has been created to design a systematic project which will overcome the problem of low quality of the stabiliser bar due to the some problems at forging process at Company A, and the benefits to the companies that implementing Six Sigma application. This research has focus on one specific product which is SB 45 which is use in the Brand A car.